Playing vaccine roulette: Why the current strategy of staking everything on Covid-19 vaccines is a high-stakes wager. Issue 35 (16th August 2021) - Paul, Elisabeth; Brown, Garrett W.; Kalk, Andreas; Ridde, Valéry
Highlights: The global community has disproportionately invested in vaccines to fight Covid-19. This is at the expense of alternative strategies and health system strengthening. Social determinants and co-morbidities should be factored as part of any response strategy. Risk-benefit analysis and the precaution principle should guide vaccination policy. A more diversified response to Covid-19 and future diseases should be adopted.